Temporal transcriptomic response during arsenic stress in Herminiimonas arsenicoxydans - Arsène-Ploetze Florence; Coppee Jean-Yves; Dillies Marie-Agnès; Proux Caroline; Fardeau Marie-Laure; Koechler Sandrine; Cleiss-Arnold Jessica; Bertin Philippe N (BMC Genomics, 2010)
Abstract Background Arsenic is present in numerous ecosystems and microorganisms have developed various mechanisms to live in such hostile environments. Herminiimonas arsenicoxydans, a bacterium isolated from arsenic contaminated sludge, has acquired remarkable capabilities to cope with arsenic. In particular our previous studies have suggested the existence of a temporal induction of arsenite oxidase, a key enzyme in arsenic metabolism, in the presence of As(III). Results Microarrays were designed to compare gene transcription profiles under a temporal As(III) exposure. Transcriptome kinetic analysis demonstrated the existence of two phases in arsenic response. The expression of approximatively 14% of the whole genome was significantly affected by an As(III) early stress and 4% by an As(III) late exposure. The early response was characterized by arsenic resistance, oxidative stress, chaperone synthesis and sulfur metabolism. The late response was characterized by arsenic metabolism and associated mechanisms such as phosphate transport and motility. The major metabolic changes were confirmed by chemical, transcriptional, physiological and biochemical experiments. These early and late responses were defined as general stress response and specific response to As(III), respectively. Conclusion Gene expression patterns suggest that the exposure to As(III) induces an acute response to rapidly minimize the immediate effects of As(III). Upon a longer arsenic exposure, a broad metabolic response was induced. These data allowed to propose for the first time a kinetic model of the As(III) response in bacteria.